PEMBERDAYAAN KELUARGA DALAM DETEKSI DINI DAN PENCEGAHAN DIABETIK FOOT ULCER (DFU) - Amiruddin Amiruddin; Bustami Bustami; Anasril Anasril (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
Diabetes mellitus can cause various complications, including heart disease, nephropathy, retinopathy, and neuropathy. The main cause of foot amputation in individuals with DM is diabetic foot ulcer (DFU). The number of DM patients in Kuala Bhee village continues to increase. As of December 2023, there were 20 DM patients in Kuala Bhee village. Two DM patients suffer from diabetic foot ulcers and are undergoing wound treatment. This community service aims to increase the capacity of families in early detection and prevention of Diabetic Foot Ulcers (DFU) in Gampong Kuala Bhee, Woyla District, West Aceh Regency. The methods used were health education and training in the Ipswich Touch Test (IpTT) screening. The results of the activity showed that the education successfully increased community knowledge, and the community was able to perform screening using the Ipswich Touch Test (IpTT). Follow-up actions are needed regarding efforts to prevent Diabetic Foot Ulcers in DM patients by family members, health centers, and other relevant institutions.